O escritor em seu tempo: o autoritarismo nos romances Em liberdade, de Sil-viano Santiago e O ano da morte de Ricardo Reis, de José Saramago - RODRIGUES, Célia Aparecida Ribeiro (2012)
A reflection is made over the true intellectual public role, understood by Edward W. Said (2005) as a "status quo disturber", in a comparison between two novels: Em liberdade, by Silviano Santiago, and O ano da morte de Ricardo Reis, by José Saramago, both published in the decade of 1980, presenting plots set in the decade of 1930, in Brazil and in Portugal, a period marked, in Brazil, by the deploying of Getúlio Vargas New State, and in Portugal, by the Antonio Salazar New State, politically authoritarian and corporativist regimes. The comparative analysis of these novels, which reshape the authoritarianism historical fact, has as its goal the critical study of the speech strategies pointing to the engagement, especially in written word of the citizen-writer, as the authors, in the 1980's, highlight the authoritarianism for reflecting over the writers-characters positioning and of the intellectual in general and its role toward the authoritarian regimes. Antonio Candido (2008) argues that in order to understand the uniqueness and autonomy of the literary work it is necessary to consider the elements of the social order, as long as they interfere in the weaving of the text. This is the north to this analysis, since those authors exercise an attempt to represent social life, through the literary experimentation, as they approach the violence committed by the state against individuals, among them the intellectuals, when an interesting dialog between Literature and History comes to light. These narratives are inserted in the macro-system of the Portuguese language countries, understood by Benjamin Abdala Junior (1989) as a common field of contacts between national literary systems. Therefore, aspects like literature and world knowledge, dialog between Literature and History, engagement, historical novel, authoritarianism, plot, character, narrator, time, space, representations of the intellectual and authoring notions are approached.